tan ( arctan 2 + arctan 0 + arctan 1 + arctan 5 − arctan 2 0 1 5 )
If the value of expression above can be stated as − q p , where p and q are relatively prime positive integers. Find p + q .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Rewrite as
arctan 2 + arctan 0 + arctan 1 + arctan 5 = arctan 2 0 1 5 + arctan x .
First of all, arctan 0 = 0 , so we are left with
arctan 2 + arctan 1 + arctan 5 = arctan 2 0 1 5 + arctan x .
To solve this problem, we use complex numbers. The complex number with argument (angle with respect to the real axis) arctan 2 is 1 + 2 i , since the tangent of the argument is 1 2 . Similarly, we find that 1 + i , 1 + 5 i , and 1 + 2 0 1 5 i have arguments arctan 1 , arctan 5 , and arctan 2 0 1 5 , respectively.
Let the complex number with argument arctan x be a + b i , so that x = a b . The complex number with argument arctan 2 + arctan 1 + arctan 5 is ( 1 + 2 i ) ( 1 + i ) ( 1 + 5 i ) , while the complex number with argument arctan 2 0 1 5 + arctan x is ( 1 + 2 0 1 5 i ) ( a + b i ) . Setting these two equal and solving for a + b i yields
( 1 + 2 i ) ( 1 + i ) ( 1 + 5 i ) − 1 6 − 2 i a + b i a + b i = ( 1 + 2 0 1 5 i ) ( a + b i ) = ( 1 + 2 0 1 5 i ) ( a + b i ) = − 1 + 2 0 1 5 i 1 6 + 2 i = − 1 2 + 2 0 1 5 2 4 0 4 6 − 3 2 2 3 8 i .
Finally,
x = a b = ( 1 2 + 2 0 1 5 2 ) a ( 1 2 + 2 0 1 5 2 ) b = − 4 0 4 6 3 2 2 3 8 = − 2 0 2 3 1 6 1 1 9
and p + q = 1 6 1 1 9 + 2 0 2 3 = 1 8 1 4 2 .
NOTE: Even though the value of x we found in this solution does not satisfy
arctan 2 + arctan 0 + arctan 1 + arctan 5 = arctan 2 0 1 5 + arctan x ,
it does satisfy the equation posed in the problem, since there is no range restriction on x .
WOW!! Such a fantastic use of complex.Great
Let α = arctan 2 , β = arctan 1 , γ = arctan 0 , δ = arctan 5 and ϵ = arctan 2 0 1 5 .
Then, we have:
tan ( arctan 2 + arctan 1 + arctan 0 + arctan 5 − arctan 2 0 1 5 ) = tan ( α + β + γ + δ − ϵ ) We note that γ = arctan 0 = 0 = tan ( α + β + δ − ϵ ) = 1 − tan ( α + β ) tan ( δ − ϵ ) tan ( α + β ) + tan ( δ − ϵ ) tan ( α + β ) = 1 − tan α tan β tan α + tan β = 1 − 2 2 + 1 = − 3 tan ( δ − ϵ ) = − 5 0 3 8 1 0 0 5 = 1 − 5 0 3 8 3 ( 1 0 0 5 ) 3 − 5 0 3 8 1 0 0 5 = − 2 0 2 3 1 6 1 1 9
⇒ p + q = 1 6 1 1 9 + 2 0 2 3 = 1 8 1 4 2
Did not think like this ! :) nice solution but why it does not have upvotes? let me begin by upvoting it
Sir I guess there is some drawbacks to your solution. You have not shown that in arctanx+arctany ... We have some domain conditions and according to that our result differs by pi or -pi. Although it cancels out in this question.but it should be mentioned.
None of the solutions are correct. On the left side you have an angle greater than π, and on the right side you have an angle smaller than π/2 with another angle subtracted from it, which is clearly impossible. (Read Steven's solution first and continue) Here is the reason: graph the point a+bi=-(4046-32238i)/(1+2015^2), it lies in Quadrant II, which means that arg(a+bi)>π/2. Hence its argument cannot be the output of an arctangent function, and arg(a+bi)≠arctan(b/a). If you put in arctan(b/a), you get the angle directly opposite arg(a+bi) since they have the same tangent.
Problem Loading...
Note Loading...
Set Loading...
Just use the formula - a r c t a n x + a r c t a n y = a r c t a n ( 1 − x y x + y )
And of course, a r c t a n x − a r c t a n y = a r c t a n ( 1 + x y x − y )
Io, here you have the answer, then.